A comprehensive study of sous-vide cooked Korat chicken breast processed by various conditions: texture, compositional/structural changes, and consumer acceptance - Jaksuma Pongsetkul; Nachomkamon Saengsuk; Supatcharee Siriwong; Kanjana Thumanu; Jirawat Yongsawatdigul; Soottawat Benjakul (My University, 2024)
Korat chicken (KC), is a slow-growing crossbreed renowned for its excellent growth and firm texture. This study investigated the effect of various sous-vide (SV) conditions (60 and 70°C, 1-3 h) on their texture, protein structure and degradation, as well as consumer acceptability, with the traditional boiling served as control. Texture showed significant improvement under all SV conditions compared to the control, as demonstrated by increased water holding capacity (WHC), cooking loss, and decreased shear force, hardness, and chewiness (P < 0.05). These changes corresponded to the higher sensory scores (P < 0.05). Among the SV samples, increased temperatures and longer cooking times led to higher degradation of myofibrils and connective tissue, as evidenced by a decrease in water-, salt-soluble proteins, and soluble collagen (P < 0.05). These findings aligned with the scanning electron microscopy (SEM) results, which showed a looser muscle structure in the meat under more intense cooking conditions. Based on synchrotron radiation-based Fourier transform infrared (SR-FTIR) results, a gradual increase in antiparallel forms within the amide I bands (1700-1600 cm−1) of the total spectra with higher temperature and longer cooking times was observed (P < 0.05), while the fluctuations were observed in the changes of α-helix, β-sheet, and β-turn structures. This suggested that the antiparallel structure represented a looser configuration developing during intense SV cooking. Combined with the principal component analysis (PCA) results, the findings indicated that the suitable SV condition for KC breast meat was 70°C for varying durations (1-3 h), as it showed the strongest correlation with sensory scores, particularly in terms of tenderness. In summary, these findings provided a better understanding of molecular changes and discovered SV conditions to enhance the texture quality of the KC meat.
Keywords: Chewiness; Texture (cosmology); Myofibril; Meat and Animal Product Quality